Polyphenols and Minor Constituents in Honey from North Macedonia and Bulgaria - Bogojovska, Martina; Stefova, Marina; Petreska Stanoeva, Jasmina; Bankova, Vassya; Popova, Milena (Prof. Marin Drinov Publishing House of BAS (Bulgarian Academy of Sciences), 2022)
Honey is a highly concentrated sugar solution that is a rich source of many bioactive compounds including numerous minor constituents. Among them, polyphenols such as flavonoids and phenolic acids are the most important classes of pharmacologically active compounds. Together with other minor constituents they are also considered potential chemical markers for the botanical and geographical origin of honey as well as for its authenticity. A solid-phase extraction procedure and HPLC/DAD/MSn method has been applied for identification and quantification of minor constituents in honey from the region of Bulgaria, North Macedonia, and Greece. Solid-phase extraction using Amberlite XAD-2 as an adsorbent was used for sample preparation enabling purification and concentration of the analysed compounds, mainly polyphenols. In total, 16 compounds were identified in the 21 extracts, 3 of them hydroxycinammic acids (caffeic, p-coumaric and ferulic acid), 5 flavonoids (naringenin, chrysin, galangin, pinocembrin and pinobanksin methyl ether) as well as gluconic acid, quinic acid, ascorbic acid, phenyllactic acid, kynurenic acid and abscisic acid in its two isomeric forms. Quantification of the identified polyphenols was made by an external calibration. The results showed that the developed method presented here is suitable for obtaining qualitative and quantitative data for polyphenols of honey.